Proteolysis-targeting chimaeras (PROTACs) as pharmacological tools and therapeutic agents: advances and future challenges - Chao Wang; Yujing Zhang; Tingting Zhang; Lingyu Shi; Zhongmin Geng; Dongming Xing (Taylor & Francis Group, 2022)
Proteolysis-targeting chimaeras (PROTACs) have been developed to be an emerging technology for targeted protein degradation and attracted the favour of academic institutions, large pharmaceutical enterprises, and biotechnology companies. The mechanism is based on the inhibition of protein function by hijacking a ubiquitin E3 ligase for protein degradation. The heterobifunctional PROTACs contain a ligand for recruiting an E3 ligase, a linker, and another ligand to bind with the protein targeted for degradation. To date, PROTACs targeting ∼70 proteins, many of which are clinically validated drug targets, have been successfully developed with several in clinical trials for diseases therapy. In this review, the recent advances in PROTACs against clinically validated drug targets are summarised and the chemical structure, cellular and in vivo activity, pharmacokinetics, and pharmacodynamics of these PROTACs are highlighted. In addition, the potential advantages, challenges, and prospects of PROTACs technology in disease treatment are discussed.